Interaction between Neural and Cardiac Systems during the Execution of the Stroop Task by Young Adults: Electroencephalographic Activity and Heart Rate Variability - Soraya L. Sá Canabarro; Ana Garcia; Corina Satler; Maria Clotilde Henriques Tavares (AIMS Neuroscience, 2017)
Executive processes and heart rate variability (HRV) are supposedly regulated by an integrated inhibitory neurovisceral network mainly coordinated by the prefrontal cortex. Inhibitory control, a core executive function, is demanded by the Stroop task. This study aimed to assess the interaction between electroencephalographic activity and HRV of 50 healthy undergraduate students while performing a computerized version of the Stroop task with three stages (paradigmatic congruent – CS – and incongruent – IS – stages in addition to a stage in which words were phonetically similar to color names – PSS). Behavioral results suggested a Stroop interference effect among the stages, with greater difficulty in IS followed by PSS. A pattern of cortical activation in a frontoparietal gradient with left lateralization and involvement of the prefrontal, temporal and occipital cortices was found especially in IS and PSS, which might be correlated to executive control of behavior, inhibitory control, mental representation of words, preparation of the verbal response, and processing of visual stimuli. Mean power of brain activity (μV) was higher for IS and PSS for all tested frequency oscillations. HRV parameters of SDNN and pNN50 were smaller in PSS compared to the other stages, while rMSSD was higher for CS, suggesting higher mental stress for IS and PSS. During PSS, LF/HF ratio was negatively correlated with EEG power in frontal, central and temporal regions whilst rMSSD was positively correlated with activity in frontal and parietal regions. Therefore, marked prefrontal cortex activity was associated with parasympathetic dominance, which is in line with the integrated inhibitory neural network model. In summation, the execution of the Stroop task required increased recruitment of prefrontal cortical areas and led to high mental stress, but, as it was associated with parasympathetic dominance of HRV control, conflict was solved and subjects behaved successfully.